H PENINGKATAN LITERASI DIGITAL MELALUI WORKSHOP INTERAKTIF MEDIA DIGITAL DALAM PEMBELAJARAN BAHASA INGGRIS DI SMP PLUS AL ITTIHAT - Handayani, Sri; Lingga, Thomson Radesman; Kandagasari, Nanan; Rustandi, Encep; Fauzi, Deri Fikri; Dewi, Mutiara Indah Nirmala; Raditiyanto, Satria; Haryani, Heni; Adeliani, Cindy Sri Meidina (JURNAL PENGABDIAN KEPADA MASYARAKAT (JPKM) KEBANGSAAN, 2025)
Digitalization has brought significant changes to the teaching and learning process, especially in English language learning. By integrating technology and information communication into its activities, moreover, it provides opportunities to create more interactive and engaging learning. This community service carried out at SMP Plus Al Ittihat Garut aimed at improving digital literacy of the teachers and students. The program was conducted through seminars, workshops, and intensive mentoring methods to implement affectively the program. The results of the activity showed an increase in positive attitudes towards the use of technology, digital skills, and teachers' ability to integrate digital media into English language learning. However, the limited internet access, imbalance in the availability of digital devices, and low digital literacy among teachers and students were considered as major obstacles in optimizing activities and utilizing technology in their implementation at this school. Based on the responses and enthusiasm of teachers and students, this digital literacy activity required a good sustainability to support more effective, creative, and adaptive learning in the digital era so that it can be a strategic step in overcoming the technology gap and improving the quality of education in the rural areas with limited resources.